High-power ultrafast fiber lasers for materials processing - Eidam, Tino; Breitkopf, Sven; Herrfurth, Oliver; Stutzki, Fabian; Kienel, Marco; Haedrich, Steffen; Gaida, Christian; Limpert, Jens (Advanced Optical Technologies, 2021)
State-of-the-art fiber-laser systems can deliver femtosecond pulses at average powers beyond the kilowatt level and multi-mJ pulse energies by employing advanced large-mode-area fiber designs, chirped-pulse amplification, and the coherent combination of parallel fiber amplifiers. By using sophisticated coherent phase control, one or even several output ports can be modulated at virtually arbitrary power levels and switching speeds. In addition, an all-fiber setup for GHz-burst generation is described allowing to access an even wider range of laser parameters. The combination of all these approaches together with the robustness, efficiency, and excellent beam quality inherent to fiber-laser technology has the potential to strongly improve existing materials-processing applications.
CRIS-Team Scopus Importer:2023-04-20
Keywords: coherent combination; fast switch; fiber lasers; GHz-burst; materials processing; ultrafast